Diabetes and Its Cardiovascular Complications: Comprehensive Network and Systematic Analyses - Wu, Hao; Norton, Vikram; Cui, Kui; Zhu, Bo; Bhattacharjee, Sudarshan; Lu, Yao Wei; Wang, Beibei; Shan, Dan; Wong, Scott; Dong, Yunzhou; Chan, Siu-Lung; Cowan, Douglas; et al. (Frontiers in Cardiovascular Medicine, 2022)
Diabetes mellitus is a worldwide health problem that usually comes with severe complications. There is no cure for diabetes yet and the threat of these complications is what keeps researchers investigating mechanisms and treatments for diabetes mellitus. Due to advancements in genomics, epigenomics, proteomics, and single-cell multiomics research, considerable progress has been made toward understanding the mechanisms of diabetes mellitus. In addition, investigation of the association between diabetes and other physiological systems revealed potentially novel pathways and targets involved in the initiation and progress of diabetes. This review focuses on current advancements in studying the mechanisms of diabetes by using genomic, epigenomic, proteomic, and single-cell multiomic analysis methods. It will also focus on recent findings pertaining to the relationship between diabetes and other biological processes, and new findings on the contribution of diabetes to several pathological conditions.